HUBUNGAN PERSONAL HYGIENE DENGAN KEPUTIHAN PADA IBU RUMAH TANGGA DI DESA PURWOGONDO KALINYAMATAN - Indah Ayu Sundari; Dewi Hartinah; Edi Wibowo (Nusantara Hasana Journal, 2025)
This study aims to identify personal hygiene in housewives; identify the incidence of vaginal discharge in housewives; and analyze the relationship between personal hygiene and the incidence of vaginal discharge in housewives. Most housewives, 71.6% of respondents, reported poor personal hygiene. This indicates that personal hygiene, particularly genital hygiene, is still not optimal. While 59.1% of respondents experienced normal vaginal discharge, the incidence of abnormal vaginal discharge remained quite high at 40.9%. This suggests that vaginal discharge remains a reproductive health issue that requires greater attention. A significant correlation was found between personal hygiene and vaginal discharge among housewives in Purwogondo Kalinyamatan Village, with a p-value of 0.003 and a correlation value of r = -0.314. This indicates a low-moderate negative correlation, meaning that better personal hygiene reduces the likelihood of abnormal vaginal discharge.